Viability of Risk-return Trade-off within a South African Context - Natasha Robbetze; Matthys Johannes Swanepoel (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aimed to determine whether systematic risk and return are related to each other. It answered the research question: Is it realistic for investors to expect high returns when their investments are associated with more riskiness?Design/Methodology/Approach: Quantitative analysis was applied through a correlational research design. Secondary data were collected from the Integrated Real-time Equity System (IRESS). The Statistical Package for Social Sciences (SPSS) was utilised to measure a Pearson correlation coefficient and execute multiple regression analysis. This was done to test for the relationship between financial measurements of systematic risk and return, of sampled entities.Research findings: This research found that measures of systematic risk and return are not necessarily related when empirically analysed for sampled entities.Theoretical contribution/Originality: This paper indicated that the principle of the modern portfolio theory (MPT) should not be accepted as general truth. It should not be assumed that risk and return are linearly related in all financial markets under all economic circumstances. This premise is contrary to general financial management practice, where the MPT is universally accepted and even forms the basis of other financial theories.Research limitation: The use of the IRESS database posed a limitation in terms of sampling, as the database was frequently unable to present a complete set of data needed for statistical testing. Consequently, only 33 companies were sampled, as IRESS only made a complete set of required data available for these entities.